Paradox Management: Challenges and Alternatives of Organizations’ Failure-Success Management - Lee, Junesoo (KDI School of Public Policy and Management, 2023)
Organizational management is dynamic by nature because of the two paradoxes: (1) organizational failure can be beneficial by creating new opportunities, and (2) organizational success can be harmful by bringing in new crises. The former is the essence of failure management (FM), which asserts that organizational failure and adversity can be positively utilized. The latter is the principle of success management (SM), which emphasizes that the negative aftermath of success should be cautious about. The two approaches (FM and SM; FSM in short) help us recognize and manage a dynamic sustainability through paradoxes in our organizations. However, implementing the failure-success management (FSM) in organizations is easier said than done because there are various obstacles in and out of the organization.Internal and external stakeholders of organizations have many reasons to resist FSM, ranging from psychological hesitation and cultural prematurity to institutional setback and stakeholders’ conflict. With this in mind, this article examines the patterns and logic of the challenges of FSM, and introduces theoretical and practical alternatives to sustain FSM in organizations. In the next section, the concepts of FSM are introduced first. Then the challenges and alternatives for effective FSM will follow.